Using heuristic evaluation to improve the usability of Electronic Medical Record (EMR) mobile interface of the Cardiothoracic Surgery and Anasthesia System (CSAS) - Mohammed Salman, Hasanin; Kamaruddin, Azrina; Affendey, Lily Suriani; Mansor, Evi Indriasari; O. K. Rahmat, Rahmita Wirza; Jantan, Azrul Hazri (Penerbit Universiti Teknologi Malaysia, 2015)
This paper presents initial work on mobile user-interface for electronic medical record for cardio experts. The current problem exits when the existing system is left unused by the users, in our case the cardio surgeons due to bad user interface design which involve a heavy cognitive loads and navigation problems. Medical records contain treatment history and relevant experiences related to the patient care. In order to avoid paper based medical record (PMR) drawbacks, most industrialized nations have implemented electronic medical record (EMR). This research aims to evaluate the existing CSAS system usability using heuristic evaluation and then develop an EMR system that overcomes the interface usability problems by designing an effective user interface that is acceptable to healthcare professionals with tablets as the device. Hence, proposing a new user interface prototype taking into account the findings from the evaluation process.